Fabrication of flower-like MoS2/TiO2 hybrid as an anode material for lithium ion batteries. Issue 61 (3rd August 2017) - Zhu, Xiaoquan; Liang, Xiaoyu; Fan, Xiaobin; Su, Xintai
Abstract : The 3D Hierarchical MoS2 /TiO2 nanohybrid exhibits excellent electrochemical cycling stability and rate capability as anode material for lithium ion batteries. Abstract : A three-dimensional (3D) flower-like MoS2 /TiO2 nanohybrid was synthesized via a two-step hydrothermal method. It is found that the MoS2 /TiO2 nanohybrid is assembled with MoS2 nanosheets and TiO2 nanoparticles. The TiO2 nanoparticles are homogeneously dispersed on the MoS2 nanosheets. Moreover, the MoS2 /TiO2 nanohybrid displays excellent electrochemical performance with a high reversible capacity of 801 mA h g −1 at a current density of 100 mA g −1 after 50 cycles. It also demonstrates outstanding rate behavior with a reversible discharge capacity of 660 mA h g −1 at a current density of 1000 mA g −1 and retains a capacity of about 760 mA h g −1 as the current density is returned back to 100 mA g −1 . Compared with MoS2, the MoS2 /TiO2 nanohybrid displays enhanced cycling stability and superior rate capability. The excellent electrochemical performance may be attributed to the favorable synergistic effect between MoS2 and TiO2 . The TiO2 particles may enhance the structure stability and shorten the transport distance of ions across the surface.